2018
DOI: 10.1021/acs.joc.8b01847
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Amine-Squaramides as Organocatalysts in Michael/Hemiketalization Reactions of β,γ-Unsaturated α-Ketoesters and α,β-Unsaturated Ketones with 4-Hydroxycoumarins

Abstract: The catalytic efficiency of various aminesquaramides was tested in Michael/hemiketalization reactions of 4-hydroxycoumarines with two types of enones. Tertiary amine-squaramide organocatalysts afforded the best results regarding both activity and enantioselectivity when β,γunsaturated α-ketoesters were used as the Michael acceptors (yields up to 98%, enantioselectivities up to 90% ee). On the other hand, the primary amine-squaramides are the best choice for related reactions of 4-hydroxycoumarins with enones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…If CPME and squaramide catalyst C72 were used, product 105 was obtained in 90 % ee . Other classical solvents (dioxane, dioxane/CH 3 CN, CH 2 Cl 2 /MeOH) gave lower enantioselectivities (Scheme ) …”
Section: Organocatalysis In Green Solventsmentioning
confidence: 99%
See 2 more Smart Citations
“…If CPME and squaramide catalyst C72 were used, product 105 was obtained in 90 % ee . Other classical solvents (dioxane, dioxane/CH 3 CN, CH 2 Cl 2 /MeOH) gave lower enantioselectivities (Scheme ) …”
Section: Organocatalysis In Green Solventsmentioning
confidence: 99%
“…Our research group found that 2‐MeTHF was the most suitable reaction medium for the organocatalytic synthesis of 105 (Scheme ). Under optimized conditions, the substrate scope was extended, and eight different warfarin derivatives with potential anticoagulant activities were synthetized …”
Section: Organocatalysis In Green Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sebesta and colleagues described an enantioselective Michael/hemiketalization addition of hydroxycoumarins 1 to enones 2 and ketoesters 86 using squaramide 85 [ 62 ]. The methodology developed made it possible to obtain a mixture of open and closed forms of ( R )-warfarin ( 3a ) from a bifunctional catalyst of squaramide by the formation of an iminium ion intermediate with enone and hydrogen bonding with hydroxycoumarin ( Scheme 27a ).…”
Section: Reviewmentioning
confidence: 99%
“…α,β‐Unsaturated ketones are widely used in the field of synthetic chemistry as valuable intermediates in building complex organic molecules 1–6 . They have also drawn attention due to their broad applications in the field of food, agriculture, and medicinal industries 7–10 .…”
Section: Introductionmentioning
confidence: 99%